European farmers and participatory rural appraisal: A systematic literature review on experiences to optimize rural development. (January 2017) - Menconi, Maria Elena; Grohmann, David; Mancinelli, Claudia
Highlights: We present strengths and weaknesses in participatory rural appraisal with farmers. Methods that involve direct contact between researcher and farmer are effective. The farmer asks for recognition of his historical role of protecting local areas. Participatory rural planning requires greater empowerment of farmers. Abstract: Farmers are those who daily supervise and manage rural areas, but still their collaborations with those institutions entitled to decide the transformation of these territories are not managed properly. The experiences of participatory processes with the involvement of farmers are analyzed in many agricultural studies. A systematic review has allowed us to analyse experiences related to 35 participation paths aimed at rural regions' development. The analysis has been made on the basis of 14 variables describing the path followed and its purpose, the agricultural holding involved and the areas surveyed. The work has the objectives to identify some strengths and weaknesses in the involvement of farmers in decision-making and the strengths and weaknesses of the processes themselves. The review has shown that too often in participatory processes farmers are considered only as a source of information to be used by researchers rather than as active participants in the choices for the protection, management and transformation of the rural territory. An effective participatory rural appraisal requires greater empowerment of farmers. In general, compared to the methods and tools used, farmers are wary of paths that are too complex and prefer the use of low-tech tools. This result can be attributed to the farmers' demand of direct contact with the researchers to build trust and also to the average age of European farmers, which is pretty high. In participation contexts, it is not possible to establish standardized methods and tools, because each process should be tailored for the community that expresses it. Nevertheless, the work has highlighted the need to establish some minimum principles to avoid considering unsuccessful some participation paths which, in reality, have been only scarcely participated. In the work, these principles have been presented through the development of key questions, to which those who design the path for an effective engagement of agricultural stakeholder must respond: representativeness, empowerment, empirical knowledge, relationships, group type, numerosity and involvement stage.